2011
DOI: 10.3382/ps.2010-01068
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different rearing systems on natural immune parameters in broiler turkeys

Abstract: The aim of this study was to determine serological values of lysozyme, hemolytic complement levels (alternative pathway), and bactericidal activity of serum in turkeys kept in different rearing systems (industrial, backyard, and experimental). Results showed that the values for serum bactericidal activity and hemolytic complement levels increased with age, and their values were higher in experimental and in industrial turkeys than in turkeys reared in backyard. Lysozyme concentration showed a similar pattern; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…Such trend agrees with Franciosini et al (2011) which found a much lower lysozyme value in backyard turkey.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Such trend agrees with Franciosini et al (2011) which found a much lower lysozyme value in backyard turkey.…”
Section: Resultssupporting
confidence: 91%
“…The immune system reflects the capability to react against external stress (Broom 2006). It is difficult to establish the best immune profile but we could hypothesise that fast-growing animals, genetically selected for high production, have difficulty in adapting to the organic system (Bayyari et al 1997;Franciosini et al 2011). Our results showed that HCA were higher in slow-growing birds, intermediate in medium-and lower fast-growing birds and in CL.…”
Section: Resultsmentioning
confidence: 68%
“…Lysozyme plays an essential role in the host's innate immune system against bacterial challenge by cleaving cell wall peptidoglycan [53]. The complement molecule is an important innate immune component that can initiate innate responses and modulate adaptive immune responses [54]. Respiratory burst is an oxygen-dependent mechanism by which neutrophils kill invading pathogens [55].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the immune response, it should be pointed out that generally extensive rearing systems require adequate level of immune response due to the high environmental pressure. Many Authors in different species found that the more selected breeds show a lower immune response [26][27][28]. The activation of the immune system is energetically expensive, thus, FG birds, which are genetically selected for high production, would be less capable of coping with environmental stress.…”
Section: Oxidative Status Native Immunity Blood Parameters and Use Of Pasturementioning
confidence: 99%